Designing Digital Employee Performance Management System for PT. Kreasi Edulab Indonesia - Masfufah, Megawaty; Gustomo, Aurik (Yayasan Riset dan Pengembangan Intelektual, 2026)
This study aims to examine the implementation of the employee performance management system at PT. Edulab Indonesia, identify its main weaknesses, and analyze organizational needs and challenges in managing employee performance. The findings reveal that the current system is still managed manually using Google spreadsheets with quarterly performance recapitulation, leading to inefficiencies, low transparency, subjective evaluations, and limited audit trails, which ultimately hinder effective monitoring, data-driven decision-making, and alignment between actual performance and strategic objectives. In response, the study highlights the need for clear goal alignment across organizational, divisional, and individual levels; real-time performance monitoring; standardized and objective evaluation mechanisms; continuous and documented feedback; and stronger integration between performance evaluation outcomes and employee competency development, while also acknowledging challenges such as uneven digital literacy, resistance to change, lack of a continuous feedback culture, and infrastructure limitations. This research employs a qualitative approach through in-depth interviews and document analysis, with data analyzed using NVivo to identify key themes related to system weaknesses, organizational needs, and implementation barriers. The system design is guided by the Technology–Organization–Environment (TOE) framework and the ADKAR change management model to ensure alignment with organizational readiness, technological capability, external environment, and human factors. As a result, the study proposes step-by-step to Design Digital Employee Performance Management System (DEPMS) based on continuous feedback, comprising five core modules: digital goal setting and alignment, real-time performance monitoring dashboards, standardized digital performance evaluation, continuous feedback mechanisms, and audit trail–based reporting. The proposed system is shown to enhance performance management effectiveness by improving objectivity and transparency, accelerating decision-making, strengthening accountability, and directly linking performance evaluation outcomes to employee development, thereby supporting a more agile and data-driven organizational culture.